Manajemen Produksi Iklan Radio Dan Perancangan Sistem Penentuan Biaya Iklan Pada OZ Radio 90.8 FM Jakarta - Muhammad Rizky Ramadhan; Daniel Handoko; Jamiati KN; Velda Murdiana (Journal of Management and Creative Business, 2024)
Radio advertising is a type of advertising that is quite popular and effective for promoting products or services. However, to optimize the effectiveness of radio advertising, good radio advertising production analysis and an appropriate advertising cost determination system are needed. The research entitled "Radio Advertising Production Management and Design of a System for Determining Advertising Costs on OZ Radio 90.8 FM Jakarta" aims to find out how advertising production is managed on radio and how to design advertising cost determinations on OZ Radio 90.8 FM Jakarta. The theories used in this research are advertising, production management, advertising production management, radio advertising, determining product selling prices, methods for determining production costs, where this research uses a qualitative descriptive method with data collection techniques using semi-structured interviews. Then the data that has been obtained and collected comprehensively is then analyzed using data reduction, data presentation and data description. From the process of the research stages carried out, the results of the research can show that the production of radio advertisements and the design of the cost system at OZ Radio 90.8 FM Jakarta in producing a radio advertisement go through stages of production management starting from the planning stage to supervision. Then, the determination of advertising costs is carried out using the variable costing method as a reference in determining the cost of a radio advertisement.Affairs.customers.